2016
DOI: 10.3892/or.2016.5121
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA-UCA1 enhances cell proliferation through functioning as a ceRNA of Sox4 in esophageal cancer

Abstract: Esophageal cancer (EC) is one of the most common gastrointestinal cancers, which leads to the sixth ranking of cancer-related death. Long non-coding RNAs (lncRNAs) play pivotal roles in many biological processes. lncRNA human urothelial carcinoma associated 1 (UCA1) is significantly upregulated and functions as an important oncogene in many types of human cancers. However, the role of UCA1 in EC and its underlying mechanism remains unclear. In the present study, we demonstrated that UCA1 was significantly upre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
79
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(82 citation statements)
references
References 37 publications
(38 reference statements)
3
79
0
Order By: Relevance
“…Moreover, miR-195 directly suppressed ARL2 mRNA and protein levels in bladder tumor cells, indicating that miR-195 may be a tumor suppressor gene that decreases ARL2 expression in BC. Additionally, it has been reported that ARL2 expression was directly regulated by miR-195 in human neural progenitor cells [20]. These findings suggest that ARL2 is in turn negatively regulated by miR-195.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Moreover, miR-195 directly suppressed ARL2 mRNA and protein levels in bladder tumor cells, indicating that miR-195 may be a tumor suppressor gene that decreases ARL2 expression in BC. Additionally, it has been reported that ARL2 expression was directly regulated by miR-195 in human neural progenitor cells [20]. These findings suggest that ARL2 is in turn negatively regulated by miR-195.…”
Section: Discussionsupporting
confidence: 55%
“…Moreover, UCA1 functions as a ceRNA of miR-16 to contribute to imatinib resistance in chronic myeloid leukemia cells [19]. In addition, UCA1 promotes cellular proliferation by acting as a ceRNA against Sox4 in esophageal cancer [20]. Therefore, we hypothesized that UCA1 can also acts as a decoy miRNA in regulation of mitochondrial function in BC.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Jiao et al showed that lncRNA UCA1 enhanced cell proliferation through functioning as a ceRNA of Sox4 in esophageal cancer [12]. Lv et al showed that lncRNA Unigene56159 promoted epithelial-mesenchymal transition by acting as a ceRNA of miR-140-5p in hepatocellular carcinoma cells [13].…”
Section: Introductionmentioning
confidence: 99%
“…According to the criteria for selection mentioned above, after carefully screening the abstract and full-text of these references, finally, 14 publications (including 15 studies) [1629] were identified as eligible for the present quantitative analysis of the prognostic value of UCA1 in digestive system cancers. All included publications were written in English.…”
Section: Resultsmentioning
confidence: 99%